Validation of the Clinical Treatment Score Post–Five Years in Breast Cancer Patients for Predicting Late Distant Recurrence: A Single-Center Investigation in Korea - Lee, Jun-Hee; Lee, Se Kyung; Chae, Byung Joo; Yu, Jonghan; Lee, Jeong Eon; Kim, Seok Won; Nam, Seok Jin; Ryu, Jai Min (Frontiers in Oncology, 2021)
Background: Endocrine therapy is inevitable for hormonal-positive breast cancer patients to prevent distant metastasis. It is important to evaluate the risk of recurrence and to determine which patients are viable candidates because hormonal therapy has side effects that can include postmenopausal symptoms. The Clinical Treatment Score Post–five years (CTS5), a simple tool for selecting patients for therapy, was recently introduced; however, CTS5 was applied in validation studies only to postmenopausal women. We therefore aimed in the present investigation to validate CTS5 among premenopausal breast cancer patients. Methods: We identified patients treated between 1994 to 2014 at Samsung Medical Center in Seoul, Korea and followed up for more than 60 months after surgery by using clinicopathologic parameters. According to menopausal status, we divided the study population into two groups: pre- and postmenopausal women. After calculating CTS5 values based on some parameters, we stratified the risk rate according to CTS5 and analyzed the correlation between CTS5 value and late distant recurrence (DR) by risk. Results: Among 16,904 patients treated surgically for breast cancer, 2,605 patients with hormone receptor–positive breast cancer who received endocrine therapy were included. Of these, 1,749 (67.14%) patients were premenopausal women and the median age was 44 years old. When categorizing study participants according to CTS5 risk for late DR, 86.79% were categorized as at low risk, 5.95% were categorized as at intermediate risk, and 7.26% were categorized as at high risk. The annual rate of distant recurrence was 1.41% and was similar between pre- and postmenopausal participants (1.40 vs. 1.42). Distant metastasis-free survival was not different between the groups (hazard ratio: 0.817, 95% confidence interval: 0.547–1.221). The areas under the receiver operating characteristic curve at 10 years for premenopausal and postmenopausal patients were 61.75 (95% confidence interval: 52.97–70.53) and 72.71 (95% confidence interval: 63.30–82.12). Conclusions: Although CTS5 for overall patients was able to predict late DR, it was not prognostic in premenopausal women. A modified version of CTS5 for premenopausal women might be needed so as not to underestimate the risk of recurrence risk in Korea.